Chinese medicines in the treatment of experimental diabetic nephropathy. Issue 1 (December 2016) - Liu, Jing-Yi; Chen, Xiao-Xin; Tang, Sydney; Sze, Stephen; Feng, Yi-Bin; Lee, Kai-Fai; Zhang, Kalin
Abstract Diabetic nephropathy (DN) is a severe micro vascular complication accompanying diabetes mellitus that affects millions of people worldwide. End-stage renal disease occurs in nearly half of all DN patients, resulting in large medical costs and lost productivity. The course of DN progression is complicated, and effective and safe therapeutic strategies are desired. While the complex nature of DN renders medicines with a single therapeutic target less efficacious, Chinese medicine, with its holistic view targeting the whole system of the patient, has exhibited efficacy for DN management. This review aims to describe the experimental evidence for Chinese medicines in DN management, with an emphasis on the underlying mechanisms, and to discuss the combined use of herbs and drugs in DN treatment.